2013
DOI: 10.1155/2013/274096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl on Heat Resistance, Antibiotic Susceptibility, and Caco-2 Cell Invasion ofSalmonella

Abstract: This study evaluated the effects of NaCl on heat resistance, antibiotic susceptibility, and Caco-2 cell invasion of Salmonella. Salmonella typhimurium NCCP10812 and Salmonella enteritidis NCCP12243 were exposed to 0, 2, and 4% NaCl and to sequential increase of NaCl concentrations from 0 to 4% NaCl for 24 h at 35°C. The strains were then investigated for heat resistance (60°C), antibiotic susceptibility to eight antibiotics, and Caco-2 cell invasion efficiency. S. typhimurium NCCP10812 showed increased thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
4
24
0
Order By: Relevance
“…At 25, 30, and 35 o C, no significant (p>0.05) differences were observed between strains with respect to growth (data not shown). Different growth patterns among B. cereus strains may be caused by strain variations between the bacteria (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…At 25, 30, and 35 o C, no significant (p>0.05) differences were observed between strains with respect to growth (data not shown). Different growth patterns among B. cereus strains may be caused by strain variations between the bacteria (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Our present study verified that the growth rate of six (Volker, Mach, Schmid, & Hecker, 1992), and Escherichia coli (Gunasekera, Csonka, & Paliy, 2008), have also reported that activation of the salt stress response conferred cross-protection against other stresses, that is, increased resistance to heat and H 2 O 2 . Recently, Yuan, Agoston, Lee, Lee, & Yuk, (2012) and Yoon et al, (2013) also showed that the heat resistance of Salmonella enterica was increased after exposure to NaCl. Moreover, it is evident that growing Vibrio harveyi in LB broth supplemented with 2% NaCl (34.2 mmol L −1 ) resulted in increased resistance to menadione killing compared with the same organism grown in normal LB broth (Vattanaviboon, Panmanee, & Mongkolsuk, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that exposure to NaCl can influence the adaptive survival and virulence of pathogenic bacteria. The relevance of this has been shown in Salmonella enterica serovar Typhimurium (12) , Staphylococcus aureus (Park et al., ), and Listeria monocytogenes (Garner, James, Callahan, Wiedmann, & Boor, ), whereby bacteria cultured in medium‐containing high NaCl show increased heat tolerance (Park et al., ; Yoon, Park, Oh, Choi, & Yoon, ), antibiotic resistance (Yoon et al., ), and invasion ability into host cells (Garner et al., ; Yoon et al., ). Our previous study also showed that B. pseudomallei grown under salt stress displayed significantly greater resistance to the antibiotic ceftazidime (Pumirat et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NaCl-exposed E. coli O157:H7 NCCP11142 was heat resistant, and could survive at 50℃ ( Lee et al , 2015 ). Also, Yoon et al (2013) showed that heat resistance in Salmonella Typhimurium exposed to high NaCl concentration was increased.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the invasive capability of L. monocytogenes , invasion assay using various human epithelial cell lines was usually performed, and the invasion efficiency was influenced by several stresses ( Garner et al , 2006 ; Lee et al , 2013 ). Yoon et al (2013) demonstrated that S . Typhimurium exposed to high NaCl concentration increased invasion efficiency into Caco-2 cells.…”
Section: Introductionmentioning
confidence: 99%